Correcting for Biogenic Gas Matrix Effects on Laser‐Based Pore Water‐Vapor Stable Isotope Measurements. Issue 1 (12th April 2018) - Gralher, Benjamin; Herbstritt, Barbara; Weiler, Markus; Wassenaar, Leonard I.; Stumpp, Christine
Abstract : Core Ideas: Observed biases were gas matrix effects exclusively caused by biogenic headspace CO2 . Observed biases exceeded 30× (δ 2 H) and 65× (δ 18 O) accepted measurement uncertainties. The proposed correction scheme uses data from repeated analyses of soil samples only. Post‐correction quality of isotope data matches accepted measurement uncertainties. The presented method helps to avoid grave misinterpretations of soil water isotope data. The isotopic composition (δ 2 H, δ 18 O) of pore water is an invaluable tracer for the minimally invasive study of subsurface water flow and transport processes. Here, we evaluated a method for pore water isotope analysis that combines laser‐based isotope analyzers and water‐vapor isotope equilibration using evaporation‐proof metalized sample bags. We tested inflation atmospheres (dry air vs. pure N2 ) and the impact of biogenic gas (CO2, CH4 ) accumulation for storage times of up to 4 wk. Samples were analyzed with a water isotope analyzer (Picarro L2120‐ i ) and a gas chromatograph. Air‐inflated water vapor samples showed a greater range of gas matrix effects (δ 18 O: 9.63‰; δ 2 H: 21.7‰) than N2 –inflated samples (δ 18 O: 7.49‰; δ 2 H: 10.6‰) induced by nonuniform buildup of biogenic CO2, starting immediately after sample preparation. However, only air‐inflated samples could be reliably corrected using instrument‐specific sensitivity factors that were empirically determined by interpretation of periodically repeated isotope measurements. Corrected water isotope data were confirmed by similarity with local precipitation and suction cup isotope data. Residual uncertainties were well below the natural variations of soil water isotope values and independent of storage time, thus allowing for consistently reliable interpretations of soil water isotope profiles. We conclude that, especially for pore water sampling that requires small sample volumes and/or long storage times, metalized sample bags should be used to prevent evaporation notwithstanding the enhanced buildup of biogenic gases. Further, if gas matrix effects cannot be excluded, air inflation is preferred over pure N2, as only in that case can reliable postcorrections be performed by using internal data only.